Efektivitas Program Pengembangan Kecerdasan Emosi dalam Meningkatkan Kemampuan Resiliensi Berbasis Teknologi Informasi Perserta Didik Kelas XI IPS MAN 1 Padang - Mardiyah Sabrina; Helma Helma; Rila Rahma Mulyani (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2022)
This research is motivated by the presence of students who are less able to manage emotions during online learning and the absence of an IT-based emotional intelligence development program as an effort to implement the 4.0 industrial revolution era in schools. The purpose of this research is to test the effectiveness of the emotional intelligence development program in the resilience abilities of participants. educated in the form of IT. The type of research used is experimental. The population in this study were 70 students of class XI IPS. Sampling in this study used total sampling with a sample of 35 students in the experimental group and 35 students in the control group. The results showed that: An effective information technology-based emotional intelligence development program significantly improves the resilience abilities of students in class XI IPS MAN 1 Padang. This can be proven by the results of hypothesis testing which shows that the significance value obtained is 0.035 which is smaller than the 0.050 significance determination.